Contact Challenge of Cattle with Foot-and-Mouth Disease Virus Validates the Role of the Nasopharyngeal Epithelium as the Site of Primary and Persistent Infection - Carolina Stenfeldt (American Society for Microbiology, 2018)
ABSTRACT The pathogenesis of foot-and-mouth disease virus (FMDV) in cattle was investigated through early and late stages of infection by use of an optimized experimental model for controlled contact exposure. Time-limited exposure of cattle to FMDV-infected pigs led to primary FMDV infection of the nasopharyngeal mucosa in both vaccinated and nonvaccinated cattle. In nonvaccinated cattle, the infection generalized rapidly to cause clinical disease, without apparent virus amplification in the lungs prior to establishment of viremia. Vaccinated cattle were protected against clinical disease and viremia; however, all vaccinated cattle were subclinically infected, and persistent infection occurred at similarly high prevalences in both animal cohorts. Infection dynamics in cattle were consistent and synchronous and comparable to those of simulated natural and needle inoculation systems. However, the current experimental model utilizes a natural route of virus exposure and is therefore superior for investigations of disease pathogenesis and host response. Deep sequencing of viruses obtained during early infection of pigs and cattle indicated that virus populations sampled from sites of primary infection were markedly more diverse than viruses from vesicular lesions of cattle, suggesting the occurrence of substantial bottlenecks associated with vesicle formation. These data expand previous knowledge of FMDV pathogenesis in cattle and provide novel insights for validation of inoculation models of bovine FMD studies. IMPORTANCE Foot-and-mouth disease virus (FMDV) is an important livestock pathogen that is often described as the greatest constraint to global trade in animal products. The present study utilized a standardized pig-to-cow contact exposure model to demonstrate that FMDV infection of cattle initiates in the nasopharyngeal mucosa following natural virus exposure. Furthermore, this work confirmed the role of the bovine nasopharyngeal mucosa as the site of persistent FMDV infection in vaccinated and nonvaccinated cattle. The critical output of this study validates previous studies that have used simulated natural inoculation models to characterize FMDV pathogenesis in cattle and emphasizes the importance of continued research of the unique virus-host interactions that occur within the bovine nasopharynx. Specifically, vaccines and biotherapeutic countermeasures designed to prevent nasopharyngeal infection of vaccinated animals could contribute to substantially improved control of FMDV.